Answer:
- (4x + 3)(5x - 7)
Explanation:
Given
- 20x² + 13x + 21 ( factor out - 1 from each term )
= - (20x² - 13x - 21) ← factor the quadratic
Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term
product = 20 × - 21 = - 420 and sum = - 13
The factors are + 15 and - 28
Use these factors to split the x- term
20x² + 15x - 28x - 21 ( factor the first/second and third/fourth terms )
= 5x(4x + 3) - 7(4x + 3) ← factor out (4x + 3) from each term
= (4x + 3)(5x - 7)
Thus
- 20x² + 13x + 21
= - (4x + 3)(5x - 7)